Kiekybinė bendrojo lavinimo mokyklos vadovėlių informacinių priemonių analizė - Svėrienė, Audronė (Knygotyra, 2003)
The article presents a quantitative analysis of preliminary pages in Lithuanian, German, French and Danish history and geography textbooks. The research of preliminary pages in Lithuanian and foreign textbooks shows the publishing culture of the textbook. Publishers sometimes fail to take into account publishing standards and requirements. The preliminary pages are related to other elements of the textbook structure - text and paratext - and they are used to activate students’ cognitive activity and to realise different functions of the textbook. The research was accomplished at the Georg Eckert Institute for International Textbook Research (Braunschweig, Germany). Quantitative and comparative analysis was used to analyze 160 history textbooks (student’s books) and 80 geography textbooks for V-XII grade published in 1990-2002. The results of analysis show certain differences between Lithuanian and foreign textbooks. Nearly all Lithuanian and foreign textbooks have a table of contents. More than half of them have a foreword, a preface, a glossary and a bibliography. French and German textbooks differ from the others not only in their structure, but also in their glossary and sources. In Danish history textbooks indexes are very common. Indexes and sources in Lithuanian textbooks are used less. This suggests that often there are many possibilities in creating and editing more suitable textbooks in Lithuania.